Arachidonic Acid and Freshly Isolated Human Bone Marrow Mononuclear Cells - Y. Denizot; V. Desplat; C. Dulery; F. Trimoreau; V. Praloran (Mediators of Inflammation)
Arachidonic acid (AA), a fatty acid found in the human bone marrow plasma, is the precursor of eicosanoids that modulate bone marrow haematopoiesis. To further our understanding of the role of AA in the bone marrow physiology, we have assessed its incorporation in human bone marrow mononuclear cells. Gas chromatography analysis indicates the presence of AA in their fatty acid composition. In bone marrow mononuclear cells, [3H]-AA is incorporated into triglycerides and is later delivered into phospholipids, a result not observed with blood mononuclear cells. Prelabelling-chase experiments indicate a trafficking of labelled AA from phosphatidylcholine to phosphatidylethanolamine. Stimulation of prelabelled bone marrow mononuclear cells with granulocyte-macrophage colony-stimulating factor (GM-CSF) results in the release of a part of the incorporated labelled AA. Finally, exogenous AA (up to 1 μM) has no significant effect on cell growth. In conclusion, human bone marrow mononuclear cells participate to the control of marrow AA concentrations by incorporating AA into phospholipids and triglycerides. In turn, bone marrow mononuclear cells can release AA in response to the potent haematopoietic growth factor GM-CSF.